limx->pi/4 {tan(x)-1}/(pi-4x)(adsbygoogle = window.adsbygoogle || []).push({});

I tried to solve it like this:

lim x->pi/4 tan(pi-4x)=

lim x->pi/4 tan(pi-5x+x)

= limx->pi\4 {tanx+tan(pi-5x)}/{1-tan(pi-5x)tanx}

Now

lim x->pi/4 tan(pi-4x)=(pi-4x)

Therefore,

lim x->pi/4 (pi-4x)= lim x->pi/4 (tan(x)-1)/2 [Valid as lim fx/gx=limfx/limgx and lim (fx-gx)=limfx-limgx]

hence

lim x->pi/4 {tan(x)-1}/{pi-4x}=2

But this is wrong

the answer is 1/2

Could someone please point out the mistake in my procedure

Isnt the statement lim x->a (fx -gx)=lim x->a fx-1 where g(a)=1 coorect?

Thanks

**Physics Forums | Science Articles, Homework Help, Discussion**

Join Physics Forums Today!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

# Question on Limit of a given function

**Physics Forums | Science Articles, Homework Help, Discussion**